Optogenetics and its application in pain and anxiety research. (October 2019) - Jarrin, Sarah; Finn, David P.
Graphical abstract: Highlights: Optogenetics is a research tool that allows for real-time neuromodulation of specific neuronal populations in awake behaving animals. In vivo optogenetic neuromodulation enables investigation of the role of neural pathways in models of pain and anxiety. Optogenetics has identified key roles of specific neuronal subtypes in discrete brain regions including the mFPC and amygdala in pain and anxiety. Abstract: Chronic pain and anxiety can be debilitating disorders and are often comorbid. There is significant overlap in the neural circuitry of pain and anxiety. Current treatments for these disorders are often ineffective and have negative side-effects, making further research into pain and anxiety circuitry crucial. The technique of optogenetics is propelling the possibilities for functional neuroanatomical research. With the use of light-activated proteins called opsins, optogenetics enables the switching on or off of a selective population of neurons, with precise temporal control. This manuscript reviews recent research that has employed optogenetic methodology to advance understanding of the neural circuitry of pain and anxiety and identify novel approaches for their improved treatment.